Ecobrick: solusi cerdas dan kreatif untuk mengatasi sampah plastik - Sekartaji Suminto (Institut Seni Indonesia Yogyakarta, 2017)
Plastics are widely used in various needs of human life, starting from food wrapping material to the needs of automotive materials. Plastic is the most popular material and most widely used as a material for automotive component making, in addition to metal in the form of iron. The most important problem of plastics is the plastic waste that can not decompose naturally. It takes a very long time to clean up plastic waste from the face of the earth, especially since the use of plastic is almost unmanageable. Plastics also make the air temperature hotter day by day, due to its non-porous polymeric properties. At the moment, most products are produced without thinking of where they are going when consumed. Many products are also designed to fail within a certain period known as